Desiderio di comunità (Mantichora. Italian Journal of Performance Studies, 2025)
The article analyses, by relating the studies on Performance by R. Schechner andthe aesthetics of the void by J. Lacan, the way in which human beings have always looked for significant objects to give meaning to their existence and their fundamental emptiness, starting from the first detachment from the maternal, as well as from the entry into the world of the symbolic. We will talk specifically about the “Quaderni Aperti” association. The work of this group of artists, scholars and socio-cultural workers, concerns the collection of notebooks of elementary school children from the nineteenth century to today, in 35 countries around the world. The notebooks, due to the work of re-signification to which they were subjected, have taken on a transitory (Winnicott 1971) and significant function. The performative activities (R. Schechner 2002, V.Turner 1982) proposed starting from this object, make the work of this group more worthy of attention than ever.